Are particular industries more likely to succeed? A comparative analysis of VC investment in the US and Europe - Roman Kraeussl; Stefan Krause (Goethe University Frankfurt, Center for Financial Studies (CFS), 2010)
The objective of this study is to determine whether specific industries across countries or within countries are more likely to reach a stage of profitability and make a successful exit. In particular, we assess whether firms in certain industries are more prone to exit via IPO, be acquired, or exit through a leveraged buy-out. We are also interested in analyzing whether substantial differences across industries and countries arise when looking separately at the success' rate of firms which have received venture funding at the early seed and start-up stages, vis-à-vis firms that received funding at later stages. Our results suggest that, inasmuch as some of the differences in performance can be explained by country-specific factors, there are also important idiosyncratic differences across industries: In particular, firms in the biotech and the medical / health / life science sectors tend to be significantly more likely to have a successful exit via IPO, while firms in the computer industry and communications and media are more prone to exit via merger or acquisition. Key differences across industries also emerge when considering infant versus mature firms, and their preferred exit.
urn:nbn:de:hebis:30-75139
Keywords: G24; G3; 330; Venture Capital; Success Rates; Country Comparison; Industry Comparison; Biotech Firms; Risikokapital; Branche; Unternehmensgründung; Unternehmensentwicklung; Erfolgsfaktor; Schätzung; Biotechnische Industrie; IT-Industrie; USA; Europa